Assessing the Effects of Exposure to Supermax Confinement on Offender Postrelease Behaviors. (June 2017) - Butler, H. Daniel; Steiner, Benjamin; Makarios, Matthew D.; Travis, Lawrence F.
A number of studies have examined whether the carceral experience has a criminogenic, deterrent, or null effect on offenders' postrelease behaviors, but it is less clear whether exposure to different types of confinement similarly affects offenders' postrelease behaviors. Using data collected from offenders released under postrelease supervision in Ohio, we examine the impact of exposure to one type of penal environment, supermax confinement, on offenders' odds of recidivism and other postrelease outcomes. The findings revealed that exposure to supermax confinement had no impact on offenders' postrelease behaviors.